Development of network location in the state of Uncertainty (ROBUST State) - Alireza Alinajad; Samrand Salari; Azadeh Seif (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2012)
This research investigates issues relating to facilities location whichcovers network design under the conditions of uncertainty and robuststate. In this direction a model is developed in which lack of certaintyis taken into consideration regarding parameters such as demand andvarious costs. Unlike the classical methods that the structure ofnetwork is predefined and is predetermined, the facilities locationmakes decisions with respect to the structure of the network.The discussed issue in many real and actual applications such as roadsnetwork, communication systems and etc does exist and locating thefacilities and designing the main network simultaneously areconsidered as important factors; therefore redesigning andoptimization of models which look for simultaneous solutions seemessential. There have been various strategies in the literature ofuncertainty optimization. Two of the most important strategies are the“Probabilistic Optimization” and “Robust Optimization”.This article employs the robust optimization to resolve the uncertaintyand the modelization arguments. Moreover using random samples, thedeveloped model is validated and for further mathematical analysis isutilized